Schema therapy for personality disorders in autistic adults: Results of a multiple case series study. (28th December 2022) - Vuijk, Richard; Deen, Mathijs; Geurts, Hilde M.; Arntz, Arnoud
Abstract: Background: To our knowledge, treatment of personality disorder (PD) comorbidity in autistic adults is understudied and is still in its infancy. We investigated the effectiveness of schema therapy (ST) for autistic adults with PD. Method: A multiple case series design with 12 adults (aged 19–62 years) was used with baseline, exploration, ST (with cognitive behavioural and experiential techniques) and follow‐up conditions. Participants rated dysfunctional core beliefs (primary outcome) weekly during baseline and treatment and monthly during follow‐up. Schema modes, general mental health symptoms, social responsiveness, PD traits and common Axis‐I mental disorders were assessed. Results: Mixed model analyses indicated significant effects of ST with medium to large effect sizes for dysfunctional core beliefs, functional schema modes, PD traits, general mental health symptoms and social responsiveness. Results remained stable during follow‐up. Conclusion: The results of this study indicate that ST might be effective in decreasing dysfunctional core beliefs, PD traits and general mental health symptoms and in increasing functional schema modes and social responsiveness. Improvements persisted over time. ST seems effective in treating PD in autistic individuals.